PEMETAAN RUANG ADAT (KEARIFAN LOKAL) KAMPUNG AYAPO DISTRIK SENTANI TIMUR KABUPATEN JAYAPURA - Elisabeth Wambrouw; Deasy Widyasatomo (Pusat Riset dan Inovasi Nasional, 2022)
The Map is a picture of the earth's surface that is displayed on a flat plane with a certain scale and the depiction of the earth's surface is reduced to a certain scale in the form of symbols that are selective in a certain projection system that is represented in two dimensions from a three-dimensional space. Various types of data can be described and explained in maps and provide information on the correlation of data to the geographical conditions (geospatial information) of an area which can then be used as a tool in policy formulation, in this case the customary area of ​​the Ayapo village in the East Sentani District. This research was conducted using a mapping method using spatial data based on satellite imagery from Google Earth Pro and community participation through field surveys through interviews. The data was then processed using ESRI ArcGIS software. The research was conducted in the Ayapo traditional village, Jayapura Regency, Papua Province. From the results of the information depiction carried out, it was obtained a map of the Ayapo village, a mapping of the distribution of indigenous peoples which included traditional leaders and tribal chiefs as well as a map of the structure of the customary space. Mapping also obtained the development of the ayapo village for 3 years, namely 2002, 2014, and 2021 which showed the growth of the village spread out along the coast of Lake Sentani in a linear form. This customary mapping becomes a source of information for the development of traditional traditional villages in Jayapura district.